Effect of Reengineering on the Information and Statistics Process in the Iran University of Medical Sciences - Parisa Mehdizadeh; Nooredin Dopeykar; Mehdi Ebrahimnia; Maryam Yaghoubi; Mohammad Meskarpour; Manaf Abdi (International Journal of Travel Medicine and Global Health, 2014)
Introduction: Nowadays, organizations working in dynamic and competitive environments have to change their processes from both the inside and outside of the organization. One of the most effective strategies for monitoring and controlling these changes is re-engineering. This study aimed to refine the collection and classification process of data through re-engineering. Methods: This study was done with an analytical-descriptive approach in 2012, in the Planning and Budget department of the Iran University of Medical Sciences. Data were collected by documents, interviews and observations. Three main process indicators include: number of activities, time, and costs of human resource. These were calculated and compared before and after the implementation of the reengineering. Data were analyzed using Microsoft Excel 2007. Results: The current status of the process included 53 activities that reduced to 27 after reengineering. Total process time was reduced from 79 to 38 days and direct human costs decreased to about 15 million Rls. Thus, by the implementation of reengineering, the number of activities, time and costs were decreased to 49%, 52% and 54% respectively. Conclusion: Based on the findings, re-engineering led to improvements of performance and saved resources. Therefore the use of this technique is recommended in order to have an improvement in different performances, increases satisfaction and saves resources.